(untitled) (Ukrainian Journal of Ophthalmology, 2025)
This paper considers general rehabilitation. In addition, attention is given to prospects for advancement in rehabilitation in the field of ophthalmology. The following major aspects of further development of the vision rehabilitation system in Ukraine were determined: 1) organization of up-to-date process of rehabilitation in the field of healthcare requires forming specialty rehabilitation units/words for persons with visual impairments (PVAs); 2) a comprehensive and continuous process of rehabilitation for PVAs should be achieved through established relationships among the parties involved; 3) rehabilitation is not only for people whose visual impairment is permanent and irremediable, but is primarily for those whose visual impairment is potentially remediable; 4) increasing awareness of vision rehabilitation issues among ophthalmologists and rehabilitation specialists should be a strategic objective of the healthcare system; 5) rehabilitation of vision should not only involve measures for adaptation of low-vision patients to new life conditions, but also should consider a range of measures aimed at optimizing visual function, including postoperative rehabilitation, post-medication rehabilitation, surgical rehabilitation, esthetic rehabilitation (including prosthetics), etc, and 6) developing specialty rehabilitation care for PVIs and moving forward from empirical approaches to an era of evidence-based practice requires further research on the efficacy of measures of medical vision rehabilitation.